Opposing The Construction of Femininity in Неделя Как и Любой Другой by Natalya Baranskaya - Anggita, Kumara; Elfira, Mina (Humanus, 2024)
The media in Russia, particularly initiatives such as the Stakhanovite movement, has significantly contributed to promoting women's empowerment in Russia. Despite leaving a lasting influence, these efforts also resulted in unintentional outcomes, including the portrayal of women idealistically through propaganda that can be seen in one of Russian Literatures.  This article delves into the construction of femininity in Natalya Baranskaya's novel Неделя Как и Любой Другой (1969)  within the context of the Soviet state. The qualitative method is used for analysis with the aim to demonstrate that terms addressed to women in the Soviet Union were forms of propaganda rather than empowerment, aimed at shaping female characters according to the state's needs. The paper employs Gender and Nation theory by Nira Yuval-Davis (1997). The study reveals that slogans like “The Real Soviet Women” along with women-targeted questionnaires and state-imposed childbirth quotas, served as instruments employed by the government to manage women's reproductive choices, influence gender norms, and uphold patriarchal ideals. In conclusion, this critique serves as Baranskaya’s opposition against heavily enforced patriarchal systems within the Soviet government.